Answer: [tex]f(g(2))=16[/tex]
Step-by-step explanation:
Given the function [tex]f(n)[/tex]:
[tex]f(n)=2n+4[/tex]
And the function [tex]g(n)[/tex]:
[tex]g(n) = 4n - 2[/tex]
The first step we can apply is to find [tex]g(2)[/tex]. To do it, we need to substitute [tex]n=2[/tex] into the function and then we must evalute. Then, this is:
[tex]g(2) = 4(2) - 2\\\\g(2) =8 - 2\\\\g(2)= 6[/tex]
Finally, in order to find [tex]f (g(2))[/tex] we need to substitute [tex]g(2)[/tex] found above, into the function [tex]f(n)[/tex] and then we must evaluate.
So, we get:
[tex]f(g(2))=2(6)+4\\\\f(g(2))=12+4\\\\f(g(2))=16[/tex]